The effects of magnesium treatment on short-term changes in heart rate variability, ventricular function and lipid profile in streptozotocin-induced diabetic rats - Amoni, Matthew (Department of Human Biology, 2017)
INTRODUCTION: Diabetes mellitus is a major and rapidly growing worldwide health problem, causing mortality largely in developing countries such as South Africa. Diabetes induces life threatening cardiovascular complications including cardiac autonomic neuropathy, ventricular dysfunction and dyslipidaemia, which are dependent on the duration and severity of the diabetes. Most complications are identified at a late, irreversible stage following long-standing diabetes; therefore, early detection and treatment of cardiovascular complications may reverse impairments and improve outcomes. The early treatment of diabetic complications remains ineffective, as the associated underlying features, such as electrolyte disturbances, are poorly understood. A key electrolyte disturbance in diabetes is hypomagnesaemia, which is also an independent cardiovascular risk factor. However, the effects of magnesium (Mg²⁺) supplementation are unclear. Therefore, this study investigated the effects of Mg²⁺ treatment on the early manifestations of streptozotocin (STZ)-induced diabetic cardiac complications. METHODS: Adult male Wistar rats were treated once with STZ (50 mg/kg, i.p.) or vehicle (citrate), and daily for seven days with MgSO4 (270 mg/kg, i.p.) or saline. Blood glucose and body weight were monitored daily. On the eighth day, in vivo tail-pulse plethysmography was recorded for analysis of heart rate variability (HRV), a marker of cardiac autonomic function. Ex vivo, Langendorff-based left ventricular (LV) pressure-volume parameters were measured using an intraventricular balloon. Other hearts were stained with Masson's trichrome and haematoxylin and eosin for histological analysis. Cardiac tissue Mg²⁺ concentration as well as plasma lipid- and Mg²⁺ levels were measured by colorimetric assays. RESULTS: Diabetes reduced heart rate and increased the low-frequency (LF)/high-frequency (HF) power ratio. Mg²⁺ treatment prevented theses diabetes-induced changes in heart rate and in the low-frequency (LF)/high-frequency (HF) power ratio (p < 0.05, n = 9/group). In addition, Mg²⁺ restored orthostatic stress induced changes in heart rate, and LF/HF ratio in diabetic rats (p < 0.05, n = 9/group). In isolated hearts, Mg²⁺ reversed the diabetes-induced decrease in LV end-diastolic elastance (p < 0.05, n = 6/group) and the right shift of end diastolic equilibrium volume intercept from 49 ± 6 μ L to 25 ± 5 μL (p < 0.05, n = 6/group), without altering LV developed pressure or end systolic elastance. Diabetes significantly increased plasma triglyceride, total cholesterol and blood glucose (p < 0.05, n = 7/group), and significantly decreased body weight (p < 0.05, n ≥ 16/group) compared to control, but these changes were not prevented by Mg²⁺ treatment. Neither diabetes nor Mg²⁺ treatment altered plasma- and tissue Mg²⁺ levels. Histologically, diabetes and Mg²⁺ treatment also did not alter cardiomyocyte size or the amount of interstitial collagen in myocardial tissue. CONCLUSION: These results show that Mg²⁺ treatment attenuates diabetes-induced autonomic dysfunction and improves LV diastolic distensibility in short-term diabetes. However, the diabetic metabolic disturbances of hyperglycaemia and dyslipidaemia, the changes in cardiac microstructure or the plasma- and cardiac tissue Mg²⁺ levels were uninfluenced by Mg²⁺ treatment. This suggests that Mg²⁺ exerted its beneficial effects independent of these factors, highlighting the underling mechanisms remain to be clarified. The Mg²⁺ levels not measured in this study by which changes could have been mediated was intracellularly; an aspect that should be further explored in future studies. Furthermore, whether these effects would be translatable to chronic diabetes is an important next question. Thus, the results of this study suggest that Mg²⁺ may have a modulatory role in treating early diabetic cardiovascular complications, but future studies will need to clarify the underlying mechanisms.